Insights from the refugee response in Cameroon - Butel, A (Refugee Studies Centre, University of Oxford, 2013)
The integration of Central African refugees into existing Cameroonian communities has had far-reaching development impacts on the region and the state as a whole; this observation calls us to re-evaluate the significance of smaller-scale, less noticed refugee crises